2004
DOI: 10.2118/04-04-03
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Cold Heavy Oil Production With Sand by Reservoir-Wormhole Model

Abstract: FIGURE 1: Proposed time-dependent relative permeability correlation (the arrow in the curve points to the direct of more released gas).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Scholars have conducted extensive research on sand production in gas wells. , It is believed that the gas volume in a gas well is between the critical flow rate of proppant reflux in the fracture and the critical sand carrying flow rate in the wellbore, which not only avoids proppant reflux in the fracture but also reduces the probability of wellbore fluid accumulation and sand blockage in the gas well throttle and reduces the safety risks of gas well production and gathering.…”
Section: Resultsmentioning
confidence: 99%
“…Scholars have conducted extensive research on sand production in gas wells. , It is believed that the gas volume in a gas well is between the critical flow rate of proppant reflux in the fracture and the critical sand carrying flow rate in the wellbore, which not only avoids proppant reflux in the fracture but also reduces the probability of wellbore fluid accumulation and sand blockage in the gas well throttle and reduces the safety risks of gas well production and gathering.…”
Section: Resultsmentioning
confidence: 99%
“…Random walk algorithm to generate fractal wormholes (Yuen et al [14]), stress analysis and instability model of fluid and granular matrix flow (Geilikman et al [15]; Geilikman and Dusseault [16]; Wang and Chen [20]), and altering the absolute permeability and porosity in the region surrounding the production well (Denbina et al [17]; Sanyal and Al-Sammak [18]; Rivero et al [19]) are among the approaches used to model CHOPS process.…”
Section: Introductionmentioning
confidence: 99%
“…1) Equivalent Permeability Models: In these models, the production of sand was thought to lead to the development of a radial higher permeability (dilated) zone which would start at the vertical well and grow into the formation (2)(3)(4)(5) . 1) Equivalent Permeability Models: In these models, the production of sand was thought to lead to the development of a radial higher permeability (dilated) zone which would start at the vertical well and grow into the formation (2)(3)(4)(5) .…”
Section: Introductionmentioning
confidence: 99%
“…Denbina et al (3) concluded that both a dynamically enhanced absolute permeability of the formation with sand production and a suppressed gas relative permeability were required to history match the oil production from typical cold production wells. Wang and Chen (5) developed a cold production model which also takes into account the sand transport within wormholes. Wang and Chen (5) developed a cold production model which also takes into account the sand transport within wormholes.…”
Section: Introductionmentioning
confidence: 99%